Comparative effectiveness of eimeriocidal products for treatment of broiler chickens in small scale production - A. B. Dagaeva; B. M. Makhieva (Ветеринария сегодня)
There is currently almost no poultry holding where avian eimerioses, both monoinvasions and those associated with cryptosporidioses, salmonelloses and colibacte- rioses, are not reported. In view of this, the disease control is an urgent challenge that shall be approached in its entirety, using various eimeriostats, antibiotics and probiotics. Searching for new effective products with broad-spectrum antiparasitic action is one of priorities in avian eimeriosis control. Comparative tests of different combinations of eimeriocidal products, namely solicox + chicktonic, maduvet + tylosin and eimeterm + enrofloxacin, for their treatment and protective effectiveness were carried out under production conditions in broiler chickens of a poultry factory located in the Republic of Dagestan. To perform the tests, four groups of broiler chickens (one control group and three test groups, each comprising 50 chickens) were formed based on the principle of analogues. The treatment and prevention scheme adopted in the said poultry holding was used for the control group chickens. Test group 1 chickens were given solicox at a dose of 2 ml per 1 liter of drinking water in combination with chicktonic (a feed supplement) at a dose of 1 ml per 1 liter of water during 4–5 days. Group 2 chickens were given maduvet at a dose of 3−5 mg/kg of body weight with feed twice and tylosin at a dose of 5 g of powder per 10 liters of water once a day during 5 days; where necessary, the procedure was repeated in 14–16 days. Group 3 broiler chickens were given eimeterm 2.5% at a dose of 7 mg/kg of body weight with water during 2 days in combination with enrofloxacin at a dose of 3 ml per 1 liter of drinking water during 5–6 days. It is shown that a decrease in the number of clinically diseased and dead chickens was observed in the test groups after the use of eimeriocidal products that helped to improve zootechnical parameters of reared broiler chicks. Product extenseffectiveness and intens- effectiveness in different groups of chickens were as follows: Group 1 – 89.2 and 96%, Group 2 – 87.6 and 94%, Group 3 –81.4 and 96%, respectively. The clinical signs of eimeriosis were observed in the control group chickens throughout the entire period of studies, invasion extensity and intensity were 87.6 and 42.6%, respectively.